2007
DOI: 10.1016/j.jacc.2006.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Total Cholesterol Content of Erythrocyte Membranes Is Increased in Patients With Acute Coronary Syndrome

Abstract: This study shows, for the first time, that CEM is significantly higher in patients with ACS compared with CSA patients. These findings suggest a potential role of CEM as a marker of atheromatous plaque growth and vulnerability. Large ad hoc studies are required to establish the clinical importance and pathogenic significance of CEM measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 46 publications
(52 reference statements)
8
80
2
2
Order By: Relevance
“…Given this, the nature of the relationships in humans between serum cholesterol and both erythrocytes and platelets remain undefi ned outside of disease extremes, as does the broader relevance of these relationships to public health. Given that hypercholesterolemia, erythrocytosis, and thrombocytosis, as well as the membrane cholesterol content of both erythrocytes and platelets are all risk factors for cardiovascular disease (25)(26)(27)(28); there is a need for advancing our understanding of the underlying relationships between serum cholesterol and erythrocyte and platelet lineages in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, the nature of the relationships in humans between serum cholesterol and both erythrocytes and platelets remain undefi ned outside of disease extremes, as does the broader relevance of these relationships to public health. Given that hypercholesterolemia, erythrocytosis, and thrombocytosis, as well as the membrane cholesterol content of both erythrocytes and platelets are all risk factors for cardiovascular disease (25)(26)(27)(28); there is a need for advancing our understanding of the underlying relationships between serum cholesterol and erythrocyte and platelet lineages in humans.…”
Section: Discussionmentioning
confidence: 99%
“…If, as our data suggest, these variables track together in human subjects, it is possible that they may synergize in promoting cardiovascular disease. Indeed, emerging data suggest that erythrocytes, and erythrocyte membrane cholesterol, in particular, are independently associated with clinical instability in coronary artery disease patients ( 26,52 ). Interestingly, red blood cell distribution width, a strong prognostic marker in cardiovascular disease, is positively associated with erythrocyte membrane cholesterol ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] Cells were washed twice with ice-cold phosphate-buffered saline, scraped, and transferred into 5 ml of sucrose Buffer A (250 mM sucrose, 30 mM histidine, 1 mM EDTA-Na, pH 7.4). The cells were homogenized with a ball-bearing homogenizer.…”
Section: Purification Of Plasma Membranementioning
confidence: 99%
“…Therefore, breakdown of the erythrocytes within advanced atheromatous lesions can result in substantial cholesterol accumulation. We have previously demonstrated that-in the clinical setting-cholesterol content of erythrocyte membranes is higher in patients with acute coronary syndromes compared to those with stable coronary artery disease [18,19] . At the same time, degradation of erythrocytes inside the atheromas may lead to haemoglobin and iron release which is known to promote inflammation, further oxidation of lipids, free radicals production and activation of apoptotic pathways [13,20] .…”
Section: Erythrocytes: Mediators Of Plaque Vulnerabilitymentioning
confidence: 99%